Selecting User Influence on Twitter Data Using Skyline Query under MapReduce Framework - Ahmad Luky Ramdani; Taufik Djatna; Heru Sukoco (Universitas Ahmad Dahlan, 2018)
The aim of this research was to select and identify user influence on Twitter data. In identification stage, the method proposed in this study was matrix Twitter approach, sentiment analysis, and characterization of the opinion leader. The importan characteristics included external communication, accessibility, and innovation. Based on these characteristics and information from Twitter data through matrix Twitter and sentiment analysis, a algorithm of skyline query was constructed for the selection stage. Algorithm of skyline query selected user influence by comparing with other users according to values of each characteristic. Thus, user influence was indicated as user that was not influenced by other users in any combination of skyline objects. The use of MapReduce framework model in identification and selection stage, support whole operation where Twitter had big size data and rapid changes. The results in identification and selection of user influence exhibited that MapReduce framework minimized the execution time, whereas in parallel skyline query could reveal user influence on the data.